Les réseaux sociaux numériques comme milieu pour le développement professionnel ? - Christine Pintus; Caroline Ladage
We question the place of social networks and digital communication in the professionalization and development of nursing practices. We hypothesize that the different forms of communication by Internet via social networks can contribute to the development of professional nursing praxeologies. We seek to understand under what conditions and under what constraints these communications can play such a function. A mixed research device based on a questionnaire survey (n= 520) and the constitution of a corpus of exchanges resulting from discussion groups on social networks have allowed us to confirm the functioning in communities of practice and their interest for both students and professionals. This result encourages the consideration of the role of social networks in professional training.